(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2025)
This scientific article examines the peculiarities of administrative and legal regulation of the activities of the Situation Centre of the Ministry of Internal Affairs of Ukraine in crisis and emergency situations. Such situations include threats of a man-made, natural, health or any other nature. The functioning of this modern technical complex as a component of the state’s crisis management system aimed at ensuring the internal and external security and defence capability of Ukraine is examined. Particular attention is paid to the activities of the national risk management system in the context of emergencies, as well as the role of the Situation Centre of the Ministry of Internal Affairs of Ukraine in this system, and an assessment of its effectiveness is provided. The regulatory and legal framework governing the work of the Situation Centre of the Ministry of Internal Affairs of Ukraine is analysed, its advantages and disadvantages are identified, and problems of interagency cooperation with other state institutions are outlined. Particular attention is paid to its functioning under the legal regime of martial law. Based on the research, problematic aspects of its activities were identified and practical recommendations for improving Ukraine’s anti-crisis legislation were formulated. The implementation of the proposed changes should contribute to improving the effectiveness of the Situation Centre of the Ministry of Internal Affairs of Ukraine and strengthening the nationwide crisis management system.